Task-Oriented Programming System for Cobot-Assisted Assembly Workstations - Finkemeyer, Bernd; Luthje, Peer; Scheuer, Martin; Waller, Wiebke; Eggers, Cindy; Kasten, Jan (International Conference on Methods and Models in Automation Robot. (Online), 2023)
Robots have become indispensable in many areas. In production technology in particular, they are a valuable component. However, they reach their limits when used in small businesses. Their use is often uneconomical, especially for assembly tasks in small batches. The engineering effort is then too high in relation to the benefit. This paper presents the concept of a task-oriented robot programming system. It allows the easy creation and maintenance of robot applications for the implementation of assembly tasks. The possibilities of human-robot collaboration are an integral part of the system and extend the application portfolio. The paper explains the resulting work steps for the creation and operation of the robot application. Finally, the validation of the presented programming approach is discussed.